2022
DOI: 10.3390/su142013648
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of New Construction Material: Polymer-Stabilized Gold Ore Tailings Composite

Abstract: Recent events involving the rupture of tailings dams in Brazil have motivated the search for alternatives to incorporate the material into the production chain. At the same time, the consumption of raw materials by the civil construction sector is high, requiring the incorporation of alternative materials to achieve sustainable development. Thus, this paper proposes a new construction material based on the mechanical and microstructural behavior of polymer-stabilized and fiber-reinforced gold ore tailings comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…CHN Elemental Analysis showed that the polymer comprises 69.03% carbon, 7.01% hydrogen, and 0.52% nitrogen. The product is frequently used for pavement sealing and as a soil stabilizer [ 2 , 3 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHN Elemental Analysis showed that the polymer comprises 69.03% carbon, 7.01% hydrogen, and 0.52% nitrogen. The product is frequently used for pavement sealing and as a soil stabilizer [ 2 , 3 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…When considering the use of polymers in soil stabilization, they can be categorized into three major groups: geopolymers, biopolymers, and synthetic polymers [ 5 ]. Geopolymers are inorganic substances of aluminosilicate with combinations of other elements [ 4 , 6 , 7 ]. Biopolymers are produced based on bacteria biomass and are common in nature [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, microstructural analysis is required for a comprehensive understanding of the behavior of composites in tailings. Since tailings materials have not undergone the typical soil formation process, classical soil mechanics may not accurately represent their behavior [34][35][36][37].…”
Section: Identification Of Ksfsmentioning
confidence: 99%
“…One approach gaining a lot of attention recently is the circular economy, a concept integrating systems engineering, waste reprocessing, waste stabilization and waste repurposing to recirculate as many materials, wastes and by-products as possible back into circulation. Industrial wastes, including mine tailings [10], sludges [11], mine by-products such as clays [12] and mine waste rocks [13], have been repurposed as fillers for civil construction [14] and inert backfills [15,16] as well as reprocessed to extract base metals such as Cu [17], Au [18] and critical minerals [19]. The direct repurposing of mine tailings and industrial wastes as filler materials for construction is, however, problematic because of the possible release of heavy metals into the environment [20,21].…”
Section: Introductionmentioning
confidence: 99%